Jews and Gender - Greenspoon, Leonard (Studies in Jewish Civilization, 2021)
Jews and Gender features sixteen authors exploring the history and culture of the intersection of Judaism and gender from the biblical world to today. Topics include subversive readings of biblical texts; reappraisal of rabbinic theory and practice; women in mysticism, Chasidism, and Yiddish literature; and women in contemporary culture and politics. Accessible and comprehensive, this volume will appeal to the general reader in addition to engaging with contemporary academic scholarship.